Chronic Disease and Its Risk Factors Among Refugees and Asylees in Massachusetts, 2001-2005 - Dookeran, Nameeta M. (Centers for Disease Control and Prevention, 2010)
INTRODUCTION: Better understanding of the health problems of refugees and people who are granted political asylum (asylees) in the United States may facilitate successful resettlement. We examined the prevalence of risk factors for and diagnoses of chronic disease among these groups in Massachusetts. METHODS: We retrospectively analyzed health screening data from 4,239 adult refugees and asylees who arrived in Massachusetts from January 1, 2001, through December 31, 2005. We determined prevalence of obesity/overweight, hypertension, coronary artery disease (CAD), diabetes, and anemia. Analyses included multivariate logistic regression to determine associations between CAD and diabetes with region of origin. RESULTS: Almost half of our sample (46.8%) was obese/overweight, and 22.6% had hypertension. CAD, diabetes, and anemia were documented in 3.7%, 3.1%, and 12.8%, respectively. People from the Europe and Central Asia region were more likely than those from other regions to have CAD (odds ratio, 5.55; 95% confidence interval, 2.95-10.47). CONCLUSIONS: The prevalence of obesity/overweight and hypertension was high among refugees and asylees, but the prevalence of documented CAD and diabetes was low. We noted significant regional variations in prevalence of risk factors and chronic diseases. Future populations resettling in the United States should be linked to more resources to address their long-term health care needs and to receive culturally appropriate counseling on risk reduction.